Effect of Pilates on Glucose and Lipids: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Chen, Zehua; Ye, Xiangling; Xia, Yubo; Song, Huiting; Wang, Yi; Guan, Yingxin; Shen, Zhen; Chen, Weijian; Jiang, Tao; Wu, Huai; Xu, Xuemeng (Frontiers in Physiology, 2021)
Objective: The benefits of Pilates for blood glucose and lipids remain unclear. The purpose of this study was to examine the effect of Pilates on their levels. Methods: Searches were conducted in five databases to identify relevant articles published until October 29, 2020. Paired reviewers independently screened the articles and extracted data from each included study. Meta-analysis was performed to assess the effects of Pilates on blood glucose and lipids. Subgroup analyses and sensitivity analyses were conducted to explore heterogeneity. Results: According to the inclusion and exclusion criteria, 15 randomized controlled trials (RCTs) comprising 587 participants were included in the study. Overall, the Pilates group (PG) had a significantly greater reduction in post-prandial blood glucose than the control group (CG) (MD = −22.25 mg/dL, 95% CI: [−28.34, 16.17] mg/dL, P < 0.00001, I2 = 0%); glycated hemoglobin (HbA1c) (MD = −0.78%, 95% CI: [−1.13, −0.42]%, P < 0.0001, I2 = 88%); total cholesterol (TC) (MD = −20.90 mg/dL, 95% CI: [−37.21, −4.60] mg/dL, P = 0.01, I2 = 84%); triglycerides (TG) (MD = −12.59 mg/dL, 95% CI: [−19.88, −5.29] mg/dL, P = 0.0007, I2 = 86%); and low density lipoprotein cholesterol (LDL-C) (MD = −12.39 mg/dL, 95% CI: [−16.82, −7.95] mg/dL, P < 0.00001, I2 = 45%) compared to CG, whereas no significant difference was detected between the two groups in fasting blood glucose (MD = −7.04 mg/dL, 95% CI: [−17.26, 3.17] mg/dL, P = 0.18, I2 = 93%), insulin (MD = −1.44 μU/mL, 95% CI: [−4.30, 1.41] μU/mL, P = 0.32, I2 = 0%); and high density lipoprotein cholesterol (HDL-C) (MD = −2.68 mg/dL, 95% CI: [−9.03, 3.67] mg/dL, P = 0.41, I2 = 89%). However, by subgroup analysis, we found that compared to the CG, PG showed no significant improvement in blood glucose and lipids levels for non-diabetics, while it presented a significantly greater decrease in post-prandial blood glucose, TC, TG, and LDL-C for diabetic patients. Notably, for diabetic patients, Pilates and medication treatments showed no significant reduction in fasting blood glucose (MD = −7.00 mg/dL, 95% CI: [−26.06, 12.06] mg/dL, P = 0.40) and HbA1c (MD = −0.23%, 95% CI: [−0.58, 0.13]%, P = 0.21, I2 = 0%) than medications treatment used alone, and Pilates combined with medications and dietary treatments presented no significant improvement in fasting blood glucose than a combination of medications and dietary treatments (MD = −10.90 mg/dL, 95% CI: [−32.35, 10.54] mg/dL, P = 0.32, I2 = 94%). Conclusions: Overall, Pilates could improve post-prandial blood glucose, fasting blood glucose, HbA1c, TG, TC, and LDL-C for diabetic patients, which could be influenced by its duration and intensity. Moreover, it had no significant effect on blood glucose and lipids for non-diabetic individuals. However, Pilates, as an adjunctive treatment to medications was not superior to medications used alone in lowering fasting blood glucose and HbA1c. Furthermore, Pilates combined with medications and dietary treatments showed no significant improvement in fasting blood glucose, whereas it had a greater reduction in post-prandial blood glucose and HbA1c for diabetic patients. Systematic Review Registration:https://osf.io/xgv6w.